Metanil yellow: The toxic food colorant - Dr. Suvendu Ghosh; Debosree Ghosh; Syed Benazir Firdaus; Partha Sarathi Singha (Asian Pacific Journal of Health Sciences, 2017)
Metanil yellow is a food colorant used extensively in various foods. It is also used as an adulterant in different spices especially turmeric and regular Indian foods like pulses. Metanil yellow belongs to “non‑permitted” category of food color. Continued consumption of this toxic food color leads to adverse life‑threatening effects in humans. There are studies revealing adverse health effects of metanil yellow. Serious concern and mass awareness are needed to be raised on the issue, and use of this toxic food color needs to be abandoned completely. Key words: , ,